Education outside the classroom: Hybrid teaching-learning methods - de León Jiménez, Salvador; Zarazúa Vilchis, José Luis (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Digitalization in education, accelerated by the recent COVID-19 confinement, shows that a high proportion of learning is outside the classroom and that a post-pandemic return to a previous state in the teaching-learning process is not possible. Thus, being the objective to document how the advance of educational technology changed teaching, it is proposed: (i) to take the construct of educational modalities by curriculum to a hybrid teaching-learning process: with digital mediation and teacher mediation; (ii) and for this, the participants will have to assume responsibilities in the conduction of the new educational reality.